1986
DOI: 10.1111/j.1365-2605.1986.tb00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic evidence for deep invaginations of the lamina propria towards the seminiferous tubule lumen in a patient with varicocele

Abstract: Ultrastructural studies on biopsy tissue from the right testis of a 39-year old patient with varicocele revealed 2.5-5 microns thick invaginations of the lamina propria towards the lumen of the seminiferous tubules. These invaginations were of various lengths. The presence of invaginations was confirmed through examination of serial semi-thin sections. In some seminiferous tubules two neighbouring deep invaginations were joined together thus completely encircling and thereby separating the basal compartment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…In some cases, the membrane was separated from the seminiferous epithelium and seemed to be disrupted. Similar invaginations were observed for the first time by Haider et al [48] in the testes of patients with varicocele. They suggested that the basement membrane and the innermost one or two myoid cell layers participated in the formation of invaginations [48].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In some cases, the membrane was separated from the seminiferous epithelium and seemed to be disrupted. Similar invaginations were observed for the first time by Haider et al [48] in the testes of patients with varicocele. They suggested that the basement membrane and the innermost one or two myoid cell layers participated in the formation of invaginations [48].…”
Section: Discussionsupporting
confidence: 69%
“…Similar invaginations were observed for the first time by Haider et al [48] in the testes of patients with varicocele. They suggested that the basement membrane and the innermost one or two myoid cell layers participated in the formation of invaginations [48]. The invaginations observed in testis of experimental rats in our study contained one layer of myoid cells.…”
Section: Discussionsupporting
confidence: 69%
“…Peritubular myoid cells can also produce an extracellular matrix, shown to speci®cally increase antigen-binding protein secretion by Sertoli cells [16]. Experiments suggest that extracellular matrix and peritubular myoid cells can modulate the morphology and function of Sertoli cells [17]. Thus, nicotine might be producing disturbances in Sertoli cell function that may be The toxicity of nicotine could be caused by direct action on the reproductive structures or by indirect action through the endocrine system [9].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have also suggested that the cytoplasmic liberation of protein gene product (PGP) 9.5, a deubiquitinating enzyme, which modulates proteolysis of cell-cycle regulators, is closely associated with the [6,15,18,24]. Human basal lamina of seminiferous epithelium with cryptorchid and varicocele have been reported to be distinctly enlarged and to form invaginations toward the lumens [6,15]. Additionally, in the gonadotropin releasing hormone (GnRH) agonist-treated monkeys, basal lamina of seminiferous epithelium has been reported to be also enlarged and accompanied with diminishing spermatogenetic activity [27].…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, we thus used this animal to investigate the cellular mechanism to regulate spermatogenesis in primate, and demonstrated that the proliferation of type Ap spermatogonia is suppressed during the nonbreeding season [21]. Moreover, we have also suggested that the cytoplasmic liberation of protein gene product (PGP) 9.5, a deubiquitinating enzyme, which modulates proteolysis of cell-cycle regulators, is closely associated with the [6,15,18,24]. Human basal lamina of seminiferous epithelium with cryptorchid and varicocele have been reported to be distinctly enlarged and to form invaginations toward the lumens [6,15].…”
Section: Introductionmentioning
confidence: 99%